Output-Based Aid in Nepal : Expanding Telecommunications Service to Rural Areas - Intven, Hank; Sepúlveda, Edgardo; Howard, Curt (World Bank, Washington, DC, 2012)
A landlocked country in South Asia, Nepal has a population of around 24 million, with about 88 percent living in rural areas, and a GDP per capita of about $240. The government, headed by a prime minister, functions as a multiparty parliamentary democracy within the framework of a constitutional monarchy. In October 2002, however, the new king dismissed the prime minister and his cabinet. The king and his appointed cabinet are now governing the country until elections are held. A Maoist insurgency, launched in 1996, threatens security in much of the country, a situation exacerbated by frequent general strikes.